Efforts to Improve Mathematics Learning Outcomes Through the Question and Answer Method for Class V Students at SDN Socah 2 - Silviya Ayu Lestari; Widiyah Dwi Wulan Sari; Fitri Fatimah (Yayasan Pondok Pesantren Nurul Islam Mojokerto, 2023)
One effevtive learning method to achieve the desired student learning outcomes is through a learning process that incorporates learning strategies such as methods, models, and instructional media expected to achieve the learning objectives. Classroom action research conducted aimed to determine whether the use of question and answer methods is effective in improving student learning outcomes, especially in mathematics subjects. The results of the first cycle of research show that students are actively engaged in learning inside the classroom, but on average, they lack confidence in answering some of the questions posed. Meanwhile, in the second cycle, with the researcher's approach focusing more on the students, it can be observed that students are more actively engaged in learning and more confident in answering questions posed because during the question and answer sessions, students also participate in ice breaking activities with the hope of keeping them motivated in learning. Thus, it can be concluded that the use of the question and answer method is highly effective in the teaching of mathematics. The implementation of this method has a positive impact on the learning outcomes of fifth-grade students at Socah 1 Elementary School. Keywords: Mathematics; Question and Answer; Elementary School